THE ESSENCE OF ETHNOTOURISM, DEVELOPMENT PRECONDITIONS AND PROSPECTS IN REPUBLIC OF ARMENIA (Proceedings of the YSU C: Geological and Geographical Sciences, 2021)
The article proposes a concise and systematic theoretical framework of ethno-tourism as a separate type of tourism (definition, goals, motivational factors of the participants, development resource base, place in the tourism system, issues of sustainable development). Based on the above-mentioned theoretical provisions, the opportunities, main directions and perspective tendencies for the development of ethno-tourism in the Republic of Armenia are presented.
Keywords: ethnotourism; ethnotourist resource; ethno village; RA